Effects of preoperative and postoperative enteral nutrition on postoperative nutritional status and immune function of gastric cancer patients - Ding, Dayong; Feng, Ye; Song, Bin; Gao, Shuohui; Zhao, Jisheng (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Effects of preoperative one week enteral nutrition (EN) support on the postoperative nutritional status, immune function and inflammatory response of gastric cancer patients were investigated. Materials and Methods: 106 cases of gastric cancer patients were randomly divided into preoperative one week EN group (trial group) and early postoperative EN group (control group), which were continuously treated with EN support until the postoperative 9th day according to different treatment protocols. All the patients were checked for their body weight, skinfold thickness, upper arm circumference, white blood cell count (WBC), albumin (ALB), prealbumin (PA), C-reactive protein (CRP), humoral immunity (IgA, IgG), T cell subsets (CD4, CD8 and CD4/CD8), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), etc. on the preoperative and the postoperative 1st and 10th day, respectively. Results: PA and IgG levels of the experimental group were higher than those of the control group on the postoperative 10th day, whereas IL-6 level of the experimental group was lower than that of the control group. Conclusion: EN support for preoperative gastric cancer patients will improve the postoperative nutritional status and immune function, alleviate inflammatory response, and facilitate the recovery of patients.